Marketing Strategies and Customer Acquisition in Multipurpose Umrah Budget Fund Products: Evidence from FIF Group Amitra Syariah (Jurnal Manajemen Bisnis, 2026)
This study examines the marketing strategy of the Multipurpose Umrah Advance Fund product at the FIFGROUP AMITRA Sharia Business Unit, with a focus on customer acquisition. Using a qualitative descriptive approach, data were collected through in-depth interviews, direct observations, and analysis of internal company documents. SWOT analysis was employed to identify key internal and external factors influencing marketing effectiveness. The findings indicate that AMITRA’s primary internal strengths include strong corporate reputation, strict compliance with sharia principles, an extensive service network, and an accessible financing system. Externally, substantial market opportunities exist for Umrah financing, driven by rising public interest in religious travel, advances in digital technology, and regulatory support for the Islamic financial sector. The IFAS and EFAS analyses position AMITRA in the Strength–Opportunity (SO) quadrant, suggesting a favorable strategic posture. Accordingly, the study recommends an aggressive growth strategy that leverages internal strengths to exploit external opportunities, particularly through intensified digital marketing, strengthened partnerships with Umrah travel agencies, and the development of technology-based services to expand market reach and increase customer numbers.